Estimation of vector autoregressive models - Nebeg, Noussaiba; Bassoudi, Mohamed (Laghouat : Université Amar Telidji - Département de mathématiques, 2025)
This study aims to explore the use of Vector Autoregressive (VAR) models to analyze and predict dynamic relationships between multiple time series variables, using mathematical and statistical techniques.